Impact of the 21-Gene Recurrence Score (Oncotype DX®) on adjuvant therapy decision-making: a collaborative multicenter cohort study from Argentina - Allemand, Carola; Valerio, Ana Clara; Calvo, María Florencia; Izbizky, Gustavo; Lean, Ignacio Mc; Terrier, Francisco; Uriburu, Juan Luis; Colo, Federico; Stecher, Francisco Von; Gil, Lisandro Benitez (Mastology, 2021)
Introduction: At present, more than half of patients diagnosed with early-stage breast cancer (BC) and express hormonal receptors will receive some adjuvant chemotherapy scheme, but only a few of them would benefit in terms of survival. Genomic platforms allow a better understanding of the heterogeneity of different types of hormonal receptor-positive and HER2-negative BC. They have proven their validity as tools to identify those patients who will obtain a clear benefit with the indication of chemotherapy treatment. The aim of this study is to analyze the use of the genomic platform, namely, Oncotype Dx® and its impact on the indication of adjuvant treatment, evaluated mainly as the change in treatment indication. Methods: Multicenter observational cohort study was performed in different Mastology units in Argentina. Patients underwent the Oncotype Dx to clarify the adjuvant treatment. Treatment decisions were settled before and after performing Oncotype Dx. Results: From January 2013 to December 2018, 211 patients with luminal A or B and HER2-negative breast carcinomas, who underwent the Oncotype Dx, were included. Based on our records, 40% of the patients change the indication of adjuvant treatment after the performance of the Oncotype Dx. Of these, 24% of patients who underwent initial endocrine therapy only adjusted their treatment with the addition of chemotherapy. Among patients with an initial CTH recommendation, 49% were able to receive endocrine therapy only when, due to traditional prognostic factors, they would have received chemotherapy. Conclusions: In our population, the use of the Recurrence Score was clinically significant in relation to the change of the established treatments. Consequently, it is a very important tool and a decisive factor in the adjuvant indication in patients with positive hormonal receptors and HER2neu-negative early BC.